Early Tumor Response to Hsp90 Therapy Using HER2 PET: Comparison with (18)F-FDG PET - Smith-Jones, Peter M. (2006)
We compared (68)Ga-DOTA-F(ab′)(2)-herceptin (DOTA is 1,4,7,10-tetraazacyclododecane-N,N′,N″,N‴-tetraacetic acid [HER2 PET]) and (18)F-FDG PET for imaging of tumor response to the heat shock protein 90 (Hsp90) inhibitor 17-allylamino-17-demethoxygeldanamycin (17AAG). METHODS: Mice bearing BT474 breast tumor xenografts were scanned with (18)F-FDG PET and HER2 PET before and after 17AAG treatment and then biweekly for up to 3 wk. RESULTS: Within 24 h after treatment, a significant decrease in HER2 was measured by HER2 PET, whereas (18)F-FDG PET uptake, a measure of glycolysis, was unchanged. Marked growth inhibition occurred in treated tumors but became evident only by 11 d after treatment. Thus, Her2 downregulation occurs independently of changes in glycolysis after 17AAG therapy, and Her2 reduction more accurately predicts subsequent tumor growth inhibition. CONCLUSION: HER2 PET is an earlier predictor of tumor response to 17AAG therapy than (18)F-FDG PET.